Autoimmune diseases in the intensive care unit. An update (2013)
Autoimmune diseases (ADs) are a challenge at the intensive care unit. The management of patients with these diseases in the critical care setting has improved over time since there are new and more aggressive alternatives to treat and diagnose them. We aimed to review the current causes of admission, clinical features, outcomes and variables associated with mortality of patients with ADs admitted to the intensive care unit (ICU). International classification criteria for ADs were used to include patients. Search was done through PubMed, SCOPUS, SciELO, and LILACS databases up to December of 2011.Twenty-nine case series and forty-one case reports were analyzed after quality assessment. Respiratory involvement was the leading cause of admission. Systemic lupus erythematosus (SLE) (33.5% of reported patients), rheumatoid arthritis (25%) and systemic vasculitis (15%) were the most frequent ADs in patients admitted to the ICU in the last decade. Mortality ranged from 17% to 55% in case series including all ADs, but in the ones that only included patients with a specific AD, such as SLE, it reached up to 79%. High APACHE score, multi-organ dysfunction, older age and cytopenia were the most reported variables associated with mortality. In conclusion, ADs should always be considered in patients with life threatening conditions that warrant critical care. Variables influencing mortality should be promptly identified in order to improve the patients' outcomes. © 2012 Elsevier B.V.